Influence of Ti3SiC2 Fiber Coating on Interface and Matrix Cracking in an SiC Fiber‐Reinforced Polymer‐Derived Ceramic. Issue 8 (12th June 2015) - Filbert‐Demut, Ina; Bei, Guoping; Höschen, Till; Riesch, Johann; Travitzky, Nahum; Greil, Peter
<x xml:space="preserve">Abstract</x> The effect of Ti3SiC2 coatings on the interfacial properties of SiC‐fiber reinforced FeSiCr/SiC‐filled polymethylsilsesquioxane‐derived ceramics was investigated. An electrophoretically deposited Ti3SiC2 coating was prepared on the fiber/matrix interface. Interfacial parameters such as frictional sliding stress and fracture energy were derived from fiber push‐out tests and correlated to the thickness of the Ti3SiC2 layer. Compared to uncoated fibers, the Ti3SiC2 interlayer gives rise for a pronounced enhance of interface shear strength, coefficient of friction, and sliding strength but a reduced fracture energy. With increasing Ti3SiC2 coating thickness, thermal mismatch‐induced residual compressive stresses at the fiber/matrix interface tend to decrease significantly.